Inventaire Et Gestion Des Plantes Médicinales Dans Quatre Localités Du Niger - Soumaila Mounkaila; Barmo Soukaradji; Boube Morou; Saley Karim; Hassane Bil-Assanou Issoufou; Ali Mahamane; Kalid Ikhiri; Mahamane Saadou (European Scientific Journal, ESJ, 2017)
Objective: the present study, aims to list medicinal plants, and gathering the maximum of information concerning the therapeutic uses practised by the population and finally to determine the impact of the takings of the various organs on the survival of plants. Methodology and results: An ethnobotanic survey was driven in four municipalities in Niger, to list healing plants used by the populations. The study showed that 111 species being of 84 kinds and 48 families are used in the traditional pharmacopoeia. The main listed families are Caesalpiniaceae, Combretaceae, Fabaceae, Euphorbiaceae, Anarcadiaaceae and Rubiaceae, with respectively, 10, 7, 7, 6, 5 and 4 species. For fragments, the most used organs are sheets, barks and roots. The results of the study also show that the majority of remedies are prepared in form of decoction. The taking of organs especially roots are not without consequence for the survival of the medicinal plants according to the local population. Conclusion and research application: These results can be used for scientific research in phytochemistry and in pharmacology to go towards the development of improved traditional medicine.